2021
DOI: 10.1002/ijgo.13614
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy in the surgical management of women with endometriosis and pelvic pain

Abstract: Objective To evaluate the role of appendectomy in surgical excision of endometriosis and to assess complications associated with appendectomy. Methods Retrospective study of women undergoing appendectomy for pelvic pain and/or endometriosis during a primary gynecologic procedure. Results Record review was performed for 609 women who underwent appendectomy between 2013 and 2019 for pelvic pain (6.9%, 42/609), stage I–II endometriosis (63.7%, 388/609), or stage III–IV endometriosis (29.4%, 179/609). Appendiceal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The likelihood of appendiceal disease with endometriosis was significantly higher in women with stage III-IV endometriosis compared with those with chronic pelvic pain or in women with an abnormal appearing appendix. No complications were found related to the performance of an appendectomy [5 ▪▪ ].…”
Section: Indications For Performing An Appendectomymentioning
confidence: 89%
See 2 more Smart Citations
“…The likelihood of appendiceal disease with endometriosis was significantly higher in women with stage III-IV endometriosis compared with those with chronic pelvic pain or in women with an abnormal appearing appendix. No complications were found related to the performance of an appendectomy [5 ▪▪ ].…”
Section: Indications For Performing An Appendectomymentioning
confidence: 89%
“…In a study by Ross et al . [5 ▪▪ ], the role of appendectomy in surgical excision of endometriosis or chronic pelvic pain was assessed in a retrospective study wherein patients undergoing a laparoscopic gynaecologic procedure were consented for a possible appendectomy. The decision to perform an appendectomy was at the surgeon's discretion.…”
Section: Indications For Performing An Appendectomymentioning
confidence: 99%
See 1 more Smart Citation
“…1,6 However, the practice of concomitant appendectomy at the time of a gynecologic procedure remains controversial, and many gynecologic surgeons do not perform appendectomy due to the concern for increased risks of infection, ileus, blood loss, operating time, and morbidity. 1,2 Although single-institution studies support the safety and cost effectiveness of concomitant appendectomy in gynecologic surgery for benign indications, 1,7,8 other studies have shown increased risk of postoperative complications. 9,10 A large retrospective cohort study of patients with ovarian cancer who underwent noncytoreductive staging procedures demonstrated that patients who had concomitant appendectomy were two times more likely to have a postoperative surgical site infection.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced procedures are necessary to remove the high burden of disease; in such cases of extrapelvic endometriosis involving the anterior abdominal wall, the appendix, the diaphragm and the thorax, it may be necessary to perform additional procedures that are not traditionally performed by all gynecologic surgeons [29][30][31]. Several authors describe surgical complexity for endometriosis, which also involves the bowel, bladder, and ureters [27,32].…”
Section: Minimally Invasive Gynecologic Surgery For Endometriosismentioning
confidence: 99%